Fear and phoning: Telephones, fraud, and older adults in the UK - Button, Mark (International review of victimology, 2025)
This study explores the experiences of attempted frauds and victimisation which use largely telephone-based means of communication on predominantly over 75s in the United Kingdom. Using a postal survey targeted at the clients of a charity working mostly with this age group, two surveys were conducted during the 18-month life of the project, securing almost 2,000 responses, which sought to explore their experience of fraud as part of a wider evaluation of a fraud prevention initiative. The surveys were supported by 18 interviews with clients and 7 interviews with the charity co-ordinator and volunteers. The research found higher rates of victimisation than the norm for this group, combined with a large number of attempted frauds predominantly via the telephone, with 20% of respondents experiencing at least weekly attempts. The research highlights the first significant evidence of the fears, concerns, and anxieties among a minority of this group of frauds/scams and their impact on their daily lives. The paper also offers insights into telephone fraud and a typology of this crime.